WiMAX traffic analysis and base stations classification in terms of LRD. Issue 4 (6th May 2013) - Stolojescu‐Crisan, Cristina; Isar, Alexandru; Moga, Sorin; Lenca, Philippe
Abstract: The goal of this paper is to highlight the particularities of Worldwide Interoperability for Microwave Access (WiMAX) traffic from a long‐range dependence perspective. The application presented in this paper consists in the estimation of the quality of base stations (BS) positioning in the architecture of a WiMAX network. Analysing the traffic of the considered WiMAX network, with an original data mining methodology based on long‐range dependence, we determine which BS have a correct position in the topology of the network and which BS have an incorrect position. These BS must be repositioned when the next session of the network maintenance will take place.